2020
DOI: 10.7556/jaoa.2020.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Clarity and Completeness of Reporting in Orthopedic Clinical Practice Guidelines

Abstract: Background Clinical practice guidelines (CPGs) can positively affect the quality of patient care offered by physicians because they decrease variability in clinical practice and may help reduce unnecessary testing, promoting a more responsible use of resources. Building on existing framework for reporting guideline development, including the work of the Enhancing the Quality and Transparency of Health Research Network, the Reporting Items for Practice Guidelines in Healthcare (RIGHT) Working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…High-quality CPGs consistently scored well in rigor of development and clarity of presentation, but lower scores were observed for applicability, particularly for AAOS guidelines. These observations are in line with multiple studies on CPG quality in a wide variety of medical fields, 35,36 including AAOS guidelines 7,8 . Our study highlights the need to provide implementation toolkits to clinicians with more explicit consideration of resources, costs, and other barriers 35 .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…High-quality CPGs consistently scored well in rigor of development and clarity of presentation, but lower scores were observed for applicability, particularly for AAOS guidelines. These observations are in line with multiple studies on CPG quality in a wide variety of medical fields, 35,36 including AAOS guidelines 7,8 . Our study highlights the need to provide implementation toolkits to clinicians with more explicit consideration of resources, costs, and other barriers 35 .…”
Section: Discussionsupporting
confidence: 86%
“…These observations are in line with multiple studies on CPG quality in a wide variety of medical fields, 35,36 including AAOS guidelines. 7,8 Our study highlights the need to provide implementation toolkits to clinicians with more explicit consideration of resources, costs, and other barriers. 35 The Centers for Disease Control and Prevention provides an excellent example of focusing on CPG accessibility; they worked with early adopters to develop guidance on both how to implement and to evaluate the success of CPG recommendations in clinical practice.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…29 However, other researchers have suggested that even the highest levels of evidence supporting orthopaedic CPGs may be compromised by publication bias, financial conflicts of interest, underpowered conclusions, and low reproducibility. 4,5,11,33 Orthopaedic CPGs have found difficulties not just in production but also in adherence to the guideline's recommendations. For example, great variability in adherence to recommendations has been well established in the management of knee osteoarthritis, with authors reporting adherence rates low as 21% in some situations.…”
mentioning
confidence: 99%